Digital technologies and the mediation process: praxis in the supervised stage of the biological sciences course - Soares Junior, Celso Pinto; Sabota Silva, Barbra do Rosário; Porto, Marcelo Duarte (Cadernos de Educação Tecnologia e Sociedade, 2018)
New digital technologies are present in the historical and social context of the students. In this sense, the school environment should realize the pedagogical potential of these resources from the reinterpretation of its use and teaching mediation processes. Thus, it is essential that the initial teacherâ€™s education courses for prepare their students for professional challenges. The objective of this study is to analyze the understanding of the stages of the Biological Sciences Degree Course of the 6th Period of the State University of Goiás of the Center for Teaching and Learning in Networking, about an influence of digital technologies in education and the possible processes of pedagogical mediation To generate the data of this study, a mixed questionnaire (with open and closed questions) was used, in order to raise the understanding that future teachers have in relation to these resources and the processes of pedagogical mediation. Results allow us to affirm that theoretical knowledge is disjointed from pedagogical practice.